(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The research article focuses on the green product purchasing habits of urban and rural women consumers with particular attention to the Thoothukudi District in the Indian state of Tamil Nadu. The practise of buying environmentally friendly products, usually referred to as sustainable or green products, is known as "green purchasing behaviour" (GPB). In this work, the researcher examines how often, where, how much, and how samples of women customers purchase green products in the study area. In the study region, research has also been done to look at the relationship between demographic parameters and buying behavior among women consumers in rural and urban areas.